2000
DOI: 10.1117/12.387620
|View full text |Cite
|
Sign up to set email alerts
|

<title>Grey-value-based 3D registration of functional MRI time-series: comparison of interpolation order and similarity measure</title>

Abstract: The analysis of functional MR images of the brain such as FMRI and neuro perfusion is significantly limited by movement of the head during image acquisition. Already small motions introduce artifacts in voxel-based statistical analysis and restrict the assessment of functional information. The retrospective compensation of head motion is usually addressed by image registration techniques which spatially align the images of the time-series. In this paper we investigate the relevance of intermediate interpolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The LC value is calculated by defining a neighborhood surrounding each voxel in the reference image ( b = 0 s/mm 2 ), calculating the correlation coefficient between the reference neighborhood and the corresponding neighborhood in the image being transformed ( b > 0 s/mm 2 ) and summing these values over the image. It has been shown that only voxels with high intensity variance within their local neighborhood contribute significantly to the LC calculation and use of this fraction of the total image voxels in the optimization process reduces processing time and produces a reliable result (26). The number of voxels selected for LC calculation with respect to the total number of image voxels is referred to as the LC fraction , and typically ranges from 5%–20%.…”
Section: Methodsmentioning
confidence: 99%
“…The LC value is calculated by defining a neighborhood surrounding each voxel in the reference image ( b = 0 s/mm 2 ), calculating the correlation coefficient between the reference neighborhood and the corresponding neighborhood in the image being transformed ( b > 0 s/mm 2 ) and summing these values over the image. It has been shown that only voxels with high intensity variance within their local neighborhood contribute significantly to the LC calculation and use of this fraction of the total image voxels in the optimization process reduces processing time and produces a reliable result (26). The number of voxels selected for LC calculation with respect to the total number of image voxels is referred to as the LC fraction , and typically ranges from 5%–20%.…”
Section: Methodsmentioning
confidence: 99%
“…Consistency testing for the quantitative evaluation of registration results has already been used for matching serial brain images [24] and for time-series registration in functional MR imaging [25]. The registration consistency of a series of images is calculated as follows: given the images and , two cyclic registrations are performed:…”
Section: Consistency Testingmentioning
confidence: 99%
“…It optimized the six degrees of freedom of a rigid transformation by gradient descent with respect to normalized mutual information, a measure describing the entropy of the joint intensity histogram (Viola and Wells 1997). The software was successfully applied to other registration tasks recently (Netsch et al 2000, Wenzel et al 2010.…”
Section: Data Acquisitionmentioning
confidence: 99%